2006
DOI: 10.1159/000092073
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intracellular Magnesium and Oxygen Tension on K+-Cl- Cotransport in Normal and Sickle Human Red Cells

Abstract: In red cells from normal individuals (HbA cells), the K+-Cl- cotransporter (KCC) is inactivated by low O2 tension whilst in those from sickle cell patients (HbS cells), it remains fully active. Changes in free intracellular [Mg2+] have been proposed as a mechanism. In HbA cells, KCC activity was stimulated by Mg2+ depletion and inhibited by Mg2+ loading but the effect of O2 was independent of Mg2+. At all [Mg2+]is, the transporter was stimulated in oxygenated cells, minimally active in deoxygenated ones. By co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…35 Uncontrolled activation of the KCC has been reported in patients with sickle cell anemia and beta-thalassemia in whom pathological RBC dehydration is abundant. 36,37 Our observations show that this is also the case in the CHC patient's RBC. As for most ion transport systems, the activity of the KCC in normal RBC is down-regulated in response to cooling.…”
supporting
confidence: 65%
“…35 Uncontrolled activation of the KCC has been reported in patients with sickle cell anemia and beta-thalassemia in whom pathological RBC dehydration is abundant. 36,37 Our observations show that this is also the case in the CHC patient's RBC. As for most ion transport systems, the activity of the KCC in normal RBC is down-regulated in response to cooling.…”
supporting
confidence: 65%
“…Red cells were loaded intracellularly with Ca 2+ using the ionophore bromo‐A23187 (6 μmol/l) and extracellular [Ca 2+ ], [Ca 2+ ]o, from 0 to 10 μmol/l, clamped using appropriate Ca 2+ / EGTA (2 mmol/l) mixtures. Under these conditions, because of the Donnan ratio, free intracellular [Ca 2+ ], [Ca 2+ ] i is about double that of free extracellular values (Flatman, 1980; Muzyamba et al , 2006). Previous experiments have shown that PS exposure in Ca 2+ permeabilised red cells occurs when free [Ca 2+ ] o is increased above about 0·1 μmol/l (Weiss et al , 2012; Cytlak et al , 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Could this conformational communication be used to signal the oxygenation state to solute transporters associated with the membrane-spanning domain of band 3? The KCl cotransporter, which changes flux rate 20-fold between oxygenated and deoxygenated cells, 9 has been shown to be inhibited in DIDS-labeled cells. 49,50 Because there is no evidence that DIDS reacts with the KCl cotransporter, one possible explanation is that DIDS inhibition is mediated through an intimate association of the KCl transporter with band 3.…”
Section: Discussionmentioning
confidence: 99%
“…First, the activities of many membrane solute transporters change with the oxygen content of the cell, including volume regulatory transporters (eg, Na ϩ /H ϩ exchanger), cation coupled Cl Ϫ cotransporters, amino acid transporters, and ion channels. [1][2][3][4][5][6][7][8][9][10] The K/Cl cotransporter, for example, is reported to be 20-fold more active in oxygenated than in deoxygenated RBCs. 9,10 Second, erythrocyte metabolism is modulated by the O 2 tension of the medium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation